Implications of Bawaslu's Interpretation of the Constitutional Court Decision on the Eligibility of Former Convicts as Regional Head Candidates in Local Elections - Syarifudin, Ahmad; Septiani, Dini Lionita (Universitas Islam Negeri Raden Intan Lampung, 2023)
The Constitutional Court, in Decision No. 56/PUU-XVII/2019, reviewed Article 7 paragraph (2) letter g of the Local Election Law, setting a five-year cut-off period for prospective regional head candidates who have been sentenced to five years in prison or more. The General Elections Commission (KPU) subsequently implemented this in Regulation 9 of 2020. However, instead of adhering to the Constitutional Court’s (MK) decision and the regulation, the South Lampung General Election Supervisory Agency (Bawaslu) reinterpreted the provision stipulated in Decision No. 001/PS.REG/18.1803/IX/2020 approved a former convict previously declared Not Eligible (TMS) by the South Lampung KPU. This research examines the differing understandings of the eligibility of former convict candidates for regional head positions post the MK Decision No. 56/PUU-XVII/2019 by the South Lampung Bawaslu and its implications for the future conduct of Regional Head Elections. This normative legal study uses a case approach, focusing on MK Decision No. 56/PUU-XVII/2019 and Bawaslu Decision No. 001/PS.REG/18.1803/IX/2020. The findings reveal that the South Lampung Bawaslu misunderstood by reinterpreting the explicit provisions of Article 7 paragraph (2) letter g of the Local Election Law. This was exacerbated by using two conflicting methods of interpretation simultaneously. The implications of the South Lampung Bawaslu Decision could create legal uncertainty and the possibility of former corruption convicts slipping through as candidates, signifying a failure to ensure regional head candidates are honest, clean, and of high integrity.